Pengembangan UMKM dengan Inovasi Pengemasan dan Kemitraan di Desa Tamansari, Bogor - Wirahadi, Syahrul; Sari, Khairina; Ramadhani, Hanif Fadila; Jesika, Reni; Nugroho, Teresa Maria Judith Trianadewi; Gifari, Muhammad Luthfi Al; Wafa, Yasmin Azimah; Ismail, Muhammad; Alifa, Naila Nur; Kartika, Lindawati (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
Tamansari Village in Bogor Regency boasts a key commodity in pohpohan leaves, which has significant potential to be developed by Micro, Small, and Medium Enterprises (UMKM) into processed products such as chips through packaging innovation and partnership strategies. The UMKM